Санітарна оцінка свинини під час зберігання в умовах ринку - Самойленко, Юлія Володимирівна; Samoilenko, Yuliia (Дніпровський державний аграрно-економічний університет, 2015)
Was determined the critical shelf life of chilled pork during the implementation in the market town Sinelnikovo Dnipropetrovsk region under the control of fresh meat in the dynamics organoleptic, microbiological and biochemical parameters. Meat as a perishable product during storage may be subjected to various changes that occur as under its own enzymes (tan) or in the process of microorganisms (mucilaginized, mold, red, rot). The most dangerous kind of damage is rotting meat because proteins break down and form substances harmful to the body. Features storing meat in the refrigerator market associated with certain actions of meat while preparing it for sale, as well as during implementation, affecting the state of his health, so the shelf life of meat in the refrigerator market is limited. Established that frozen at -18 ° C in pork pieces during storage in the refrigerator market remains fresh throughout the duration of the study (12 days). As a result of the storage of meat in the market cooling chambers at temperatures +2 ... + 4°C found that the organoleptic characteristics of meat spoilage took the third day in 50% of samples, and on the 6th and 9th -in - questionable freshness of meat has been confirmed in all laboratory parameters in all samples. Differences effect on the rate of spoilage of chilled meat at different storage methods: a film in the open state is not detected. Consequently, the third day storage of chilled meat in the refrigerator market is critical. Визначено критичний термін зберігання охолодженої свинини під час реалізації в умовах ринку міста Синельникове Дніпропетровської області на підставі контролю свіжості м’яса в динаміці за органолептичними, біохімічними і мікробіологічними показниками.
Assessment of raw meat pork during storage under market
Keywords: свинина; pork; санітарна оцінка м’яса; meat health assessment; холодильні камери; refrigerators; показники свіжості м’яса; performance fresh meat; зберігання; storage